Developmental changes of the sensitivity of cardiac and liver mitochondrial permeability transition pore to calcium load and oxidative stress - Drahota, Z; Milerová, M; Endlicher, R; Rychtrmoc, D; Červinková, Z; Ošt'ádal, B (Physiological research, 2012)
Opening of the mitochondrial membrane permeability transition pore (MPTP) is an important factor in the activation of apoptotic and necrotic processes in mammalian cells. In a previous paper we have shown that cardiac mitochondria from neonatal rats are more resistant to calcium load than mitochondria from adult animals. In this study we have analyzed the ontogenetic development of this parameter both in heart and in liver mitochondria. We found that the high resistance of heart mitochondria decreases from day 14 to adulthood. On the other hand, we did not observe a similar age-dependent sensitivity in liver mitochondria, particularly in the neonatal period. Some significant but relatively smaller increase could be observed only after day 30. When compared with liver mitochondria cardiac mitochondria were more resistant also to the peroxide activating effect on calcium-induced mitochondrial swelling. These data thus indicate that the MPTP of heart mitochondria is better protected against damaging effects of the calcium load and oxidative stress. We can only speculate that the lower sensitivity to calcium-induced swelling may be related to the higher ischemic tolerance of the neonatal heart.
Keywords: Liver; Rats; játra; Mitochondrial Permeability Transition Pore; zduření mitochondrií; mitochondrie; Mitochondria, Liver; Mitochondrial Membrane Transport Proteins; přechodový pór mitochondriální permeability; vápník; jaterní mitochondrie; mužské pohlaví; Oxidative Stress; krysa rodu Rattus; Calcium; zvířata; Mitochondrial Swelling; Mitochondria; oxidační stres; transportní proteiny mitochondriální membrány; Male; Animals